Do We Pay Enough Attention to Neuropathic Pain in Knee Osteoarthritis Patients? - Majda Golob; Ivan Marković; Neno Zovko; Davorin Šakić; Ana Gudelj-Gračanin; Jadranka Morović-Vergles (Acta Clinica Croatica, 2018)
The aim of the study was to determine the prevalence of neuropathic pain in knee osteoarthritis patients using painDETECT questionnaire, and to evaluate correlations between pain intensity, gender, age and types of treatment, and the presence of neuropathic pain. The study included 122 patients. All participants completed a questionnaire on sociodemographic data, duration of symptoms, types of treatment and preventable risk factors (body mass index and waist circumference). The presence of neuropathic pain was assessed by painDETECT, according to which subjects were classified into three groups (neuropathic pain likely, possible, or unlikely). Neuropathic pain was likely in 18 (14.8%), possible in 30 (24.6%) and unlikely in 74 (60.7%) subjects. A significant positive correlation was found between visual analog scale for pain and painDETECT score. There was no statistically significant difference in gender, age, waist circumference and body mass index among three groups of participants according to painDETECT score. In conclusion, knee osteoarthritis patients with neuropathic pain component were experiencing higher levels of pain, implicating poorer pain control with common analgesics. Recognizing these patients as a distinct subgroup would allow clinicians to improve their treatment by using unconventional analgesics with central activity.